Actuators Based on Oligo[(ε-caprolactone)-co-glycolide] with Accelerated Hydrolytic Degradation. (2020) - Balk, Maria; Behl, Marc; Lendlein, Andreas
ABSTRACT: Polyester-based shape-memory polymer actuators are multifunctional materials providing reversible macroscopic shape shifts as well as hydrolytic degradability. Here, the function-function interdependencies (between shape shifts and degradation behaviour) will determine actuation performance and its life time. In this work, glycolide units were incorporated in poly(ε-caprolactone) based actuator materials in order to achieve an accelerated hydrolytic degradation and to explore the function-function relationship. Three different oligo[(ε-caprolactone)-co-glycolide] copolymers (OCGs) with similar molecular weights (10.5 ± 0.5 kg∙mol −1 ) including a glycolide content of 8, 16, and 26 mol% (ratio 1:1:1 wt%) terminated with methacrylated moieties were crosslinked. The obtained actuators provided a broad melting transition in the range from 27 to 44 °C. The hydrolytic degradation of programmed OCG actuators (200% of elongation) resulted in a reduction of sample mass to 51 wt% within 21 days at pH = 7.4 and 40 °C. Degradation results in a decrease of Tm associated to the actuating units and increasing Tm associated to the skeleton forming units. The actuation capability decreased almost linear as function of time. After 11 days of hydrolytic degradation the shape-memory functionality was lost. Accordingly, a fast degradation behaviour as required, e.g., for actuator materials intended as implant material can be realized.